Return to Learn: Academic Effects of Concussion in High School and College Student-Athletes - Holmes, Acacia; Chen, Zhongxue; Yahng, Lilian; Fletcher, David; Kawata, Keisuke (Frontiers in Pediatrics, 2020)
While awareness and understanding of concussion have improved drastically, post-concussion management in academic settings is still at its infancy. The aim of the study was to examine to what extent concussion influences on academic performance and to whether there would be a difference in concussion effects on academic performance between high-school and college students. This cross-sectional survey study included students, who were between 14 and 24 years old and sustained a sport-related concussion within the previous year. The study used a modified chain-referral sampling method, by distributing a questionnaire link to 3,000 randomly stratified athletic trainers, who worked in high school or college settings. These athletic trainers were then asked to forward the questionnaire link to students in their team, who have sustained a concussion within the previous year. The questionnaire recorded responses regarding demographics (age, sex, race/ethnicity, number of previous concussions), 22 concussion-related symptoms in a binary scale (presence/absence), perception of difficulties in math, reading, writing, computer use, and attention in a 5-point Likert scale, and asymptomatic duration of academic engagement in a 7-point Likert scale. There were 130 respondents with a history of concussion in the past year (n=59 high-school, n=71 college). While recovering from concussion, significantly more college students (84.5%) reported “difficulty concentrating” than high-school students (68.6%: p=0.049). High-school students experienced more difficulty with math than college students (p=0.002), whereas college students experienced more difficulty with reading (p=0.013) and computer use (p=0.026) than high-school students. Asymptomatic duration of cognitive activity was influenced by age (p=0.0004), where younger students were less tolerant in performing academic tasks after a concussion than older students. Our data indicate that concussions can induce negative symptoms in the academic setting regardless of age. The post-concussion difficulties in academic performance may be a grade-dependent manner, where concussions triggered difficulty in math among high school students and in reading and computer use among college students. It is clear that there is a need for guidelines and accommodations to support students with concussion in academic settings, and the guideline should reflect the age-dependent response to concussions.